Venus II. - Fol, Carine; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1988)
De Blieck, Jo ; De Clerck, Rosita Amea ; Dondeyne, Luc ; Dyck, Ward ; Dijckmans, Bruno ; Frimout, Cyr ; Grooters, Patrick ; Hullebroeck, Amaat ; Minnaert, Frans ; Szymkowicz, Charles ; Vervisch, Godfried
Venus II, Hof ter Nederloo, Sint-Pieters-Leeuw, 2 december 1988 - 22 januari 1989
boek